2020
DOI: 10.1371/journal.pone.0240311
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, expenditures, and associated factors of purchasing non-prescribed Chinese herbal medicine in Taiwan

Abstract: Background and aims Purchasing Chinese herbal medicine (CHM) without a physician’s prescription may have adverse effects on health. However, the recent status of purchasing non-prescribed CHM and the associated factors are not completely understood. We aimed to report the prevalence of purchasing CHM and associated factors. Methods Using data from the 2017 Taiwan Survey of Family Income and Expenditure, we identified 16,528 individuals (householders) aged 18 years and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…21 , 22 An analysis of data from the 2017 Taiwan Survey of Family Income and Expenditure reported that approximately 78.4% of the general population used TCM in that year. 23 Evidence also shows that the general population has turned to TCM during the COVID-19 pandemic, with one survey from Hong Kong conducted from November to December 2020 revealing that traditional, complementary and integrative medicine was commonly used there for COVID-19 prevention and treatment. 24 An animal study has indicated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes hyperinflammation in senescent cells, increases the expression of viral entry proteins and reduces antiviral gene expression, 25 which indirectly explains the high mortality rates of older adults with chronic disease who contract SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…21 , 22 An analysis of data from the 2017 Taiwan Survey of Family Income and Expenditure reported that approximately 78.4% of the general population used TCM in that year. 23 Evidence also shows that the general population has turned to TCM during the COVID-19 pandemic, with one survey from Hong Kong conducted from November to December 2020 revealing that traditional, complementary and integrative medicine was commonly used there for COVID-19 prevention and treatment. 24 An animal study has indicated that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes hyperinflammation in senescent cells, increases the expression of viral entry proteins and reduces antiviral gene expression, 25 which indirectly explains the high mortality rates of older adults with chronic disease who contract SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of these findings is not fully understood. One possible explanation is high-income patients who receive adjuvant CHM treatment may tend to seek and can afford more complementary and alternative medicine therapies, as well as having better health behaviors ( 22 ). Healthcare resources are often difficult to access in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…These physicians have a high level of expertise and integration in both Western medicine and TCM to provide patients with comprehensive care. Tai Ji and the purchase of non-prescribed CHM were not included in the clinical settings of TCM medical care and they were not covered in the national medical insurance in Taiwan [ 23 , 37 ]. Although the purchase of non-prescribed CHM is not illegal in Taiwan, TCM physicians and government discourage people to visit CHM store.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we defined the purchase of non-prescribed CHM as people purchased CHM without physician’s prescription and this phenomenon has been reported in the previous study [ 23 , 37 ]. Only physician prescribed CHM was considered as part of TCM in this study.…”
Section: Methodsmentioning
confidence: 99%